Pengembangan Modul Pembelajaran Pemesinan Bubut Berbasis E-Literacy Pada Mata Pelajaran Teknik Pemesinan Bubut - Priyas Tri Bandi; Rabiman Rabiman; Arif Bintoro Johan (Program Studi Pendidikan Vokasional Teknik Mesin, Universitas Sarjanawiyata Tamansiswa, 2023)
This study aims to: (1) create a learning module for Lathe Machining Engineering; and (2) analyze the feasibility of the lathe machining engineering module by experts. The type of research is development research (R&D). The research subjects were students of class XI SMK Nasional Berbah, while the object of the research was the e-literacy-based lathe-machining technique module. The instrument of this research was a questionnaire to provide a feasibility assessment of the lathe engineering module by material experts, media experts, subject teachers and students. The data analysis technique used descriptive statistical analysis. The results showed that the feasibility of the lathe engineering subject module from the analysis of the assessment results of the material expert lecturers I obtained an average of 3.46 in the